Plasma tetranectin as a potential clinical biomarker for epilepsy and correlation with clinical and social characteristics - Dahiya, Ekta Singh; Mehndiratta, Man Mohan; Pillai, Krishna Kolappa (International Journal of Epilepsy, 2017)
Background Tetranectin concentration has been identified as a biomarker of several types of metastatic and malignant cancers. The role of tetranectin has also be seen in some neurological disorders. We aimed to estimate the plasma tetranectin concentration in different groups of people with epilepsy (PWE) followed-up for a year. As a secondary objective, the clinical and social characteristics were also correlated with the tetranectin levels.Methods We enrolled 90 subjects grouped as Newly-diagnosed epilepsy (NDE), Drug-effective epilepsy (DEE), and Drug-refractory epilepsy (DRE) and an age-gender matched control group (n = 30). The plasma samples were collected thrice at the six-month interval and were analysed for the tetranectin concentration using S-ELISA.Results The mean plasma tetranectin levels at the baseline test were significantly lower for the DEE (6.294 ± 0.806) and DRE (7.572 ± 0.545) groups compared with control group (9.71 ± 0.628) but not the NDE group (8.651 ± 0.859 vs. 9.71 ± 0.628; p > 0.05). On a year of follow-up, the tetranectin levels for the NDE group significantly decreased (p < 0.001) matching with that of the DEE and DRE group. Multivariate linear regression analysis showed that gender (p = 0.035) in the DRE group and seizure type (p = 0.040) and diet (p = 0.046) for the NDE group were significantly correlated.Conclusion The plasma tetranectin level in PWE significantly decreased as the disease progressed irrespective of the stage of epilepsy. Thus, tetranectin could be considered as a potential progressive biomarker for epilepsy. The study outcome suggests further investigation for the possible link of tetranectin levels with clinical and social parameters.
Keywords: Tetranectin; Biomarker; Newly-diagnosed epilepsy; Drug-effective epilepsy; Drug-refractory epilepsy